(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
K-water (Korea Water Resources Corporation) operates the world’s largest Sihwa tidal power plant (254MW). Since the construction of the Sihwa Tidal Power Plant, there have been considerations for new projects utilizing existing seawalls, such as the Saemangeum Seawall, based on the potential of the west coast of South Korea. However, economic viability remains a significant challenge. Globally, countries like the UK and Russia are also exploring tidal power projects but are facing difficulties related to economic feasibility and funding. This study aims to promote the activation of new tidal power projects by analyzing the economic and policy aspects of tidal energy and examining institutional and policy utilization measures. An analysis of the Levelized Cost of Energy (LCOE) for the Sihwa Tidal Power Plant has been conducted to estimate the generation costs, along with a review of policy aspects related to industrial and technological activation. In terms of economic viability, the cost of generation was found to be 2.3 times higher compared to medium-sized solar power. From a policy perspective, tidal energy was identified as having relative advantages over other renewable energy sources. This indicates that efforts to improve institutional frameworks and create a proactive policy environment are necessary for the promotion of tidal power.